On the mass conserving solutions to the singular kernel coagulation with multi fragmentation - Das, Arijit; Saha, Jitraj (Japan Journal of Industrial and Applied Mathematics, 2022)
We investigate existence of mass conserving solutions to the coagulation and multiple fragmentation equation. The coagulation kernel is chosen from a large class of functions covering both singular and unbounded, nonsingular functions. On the other hand, fragmentation kernel includes non-singular, unbounded empirical functions. The existence proof is based on strong convergence results and it is proved with minimal restrictions over the kinetic kernels. In addition, we also prove the uniqueness property for global solution without any restriction on kinetic kernels. Moreover, the proposed results are also numerically illustrated for two well-known singular coagulation kernel